(untitled) (Hematology Meeting Reports, 2009)
During the last decade the development of new drugs for the treatment of hematologic malignancies has become really promising. This innovative drug development is based on the translation into biochemical pharmacology of specific alterations of biological functions affecting tumour cells1. One of the most important examples is imatinib: it showed that it was possible to nullify the pathognomic genetic lesion of chronic myelogenous leukemia (CML). Drugs targeting unique disease-specific pathways have also found potential applicability in treating malignancies such as CD20-positive non-Hodgkin’s lymphoma (rituximab), follicular lymphoma (Bcl-2-targeted agents2-6) and other B-cell neoplasms (splenic tyrosine kinase [Syk] inhibitors;7-9 IkB kinase inhibitors10).